Differences of Microbiomes Found in Non-Inflammatory and Inflammatory Lesions of Acne Vulgaris - Jusuf, Nelva Karmila; Putra, Imam Budi; Sari, Lovena (Clinical, cosmetic and investigational dermatology, 2020)
Bacterial activity and inflammation both influence acne vulgaris (AV) formation. is considered as an actor involved in inflammation of AV. Besides , other microbiomes found in AV may also play a role in the pathogenesis. This research was conducted to overview microbiomes found in non-inflammatory and inflammatory lesions of AV. An observational descriptive study with cross-sectional approach was designed. Sample collection was performed with 40 subjects with AV. In every patient, both non-inflammatory (closed comedone) and inflammatory (pustule) lesion samples were collected by swab. Afterward, bacterial culture was performed, continued by bacterial identification. In non-inflammatory lesions, the growth of nine bacterial species was observed from 40 samples. In an anaerobic culture, (17,5%) was identified. In aerobic cultures, different bacterial species were found including (52.5%), (12.5%), (7.5%), (7.5%), (7.5%), (5%), (5%), and (2.5%). In inflammatory lesions, nine bacterial species were found, in which was the anaerobic culture we identified (25.0%). Aerobic cultures have revealed the growth colonies of (42.5%), (22.5%), (12.5%), (10.0%), (5.0%), (2.5%), (2.5%), and (2.5%). Two mixed bacterial growths were observed in non-inflammatory lesions, while four mixed bacterial growths were found in inflammatory lesions. Differences in bacterial isolates were observed both in non-inflammatory and inflammatory lesions of AV.